Influence of exercise in children with asthma with obesity and overweight at Hospital Honorio Delgado-Arequipa - Molina Suclly, Ronald (2021)
Introduction: Bronchial asthma can be classified, as induced by physical effort (EIA) and not induced by physical effort (caused by other causes). Objective: to determine the influence of respiratory exercise in children with persistent asthma, obesity and overweight. Methods: A prospective and longitudinal case-control study was designed; It was carried out in the Pediatric Pneumology Outpatient Office of the Pediatrics Service of the Honorio Delgado Regional Hospital; from where 166 children from 6 to 11 years old were diagnosed with persistent bronchial asthma, which were divided equally into 2 groups; complying with the protocol, 25 children in the group that performed respiratory exercises and 52 children in the group that only received treatment with inhaled corticosteroids. Results: The male sex predominated in the participants, with an average age of 7.3 years, with a predominance of the moderate persistent asthma class and the majority with normal nutritional status; in the exercise-induced bronchoprovocation test, there was a similar improvement between the group that did a breathing exercise program and those that did not. Conclusion: Respiratory exercise would improve lung function in overweight asthmatic children (t = 0.2835, p = 0.777).